2001
DOI: 10.2527/2001.793698x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diets containing n-3 fatty acids on muscle long-chain n-3 fatty acid content in lambs fed low- and medium-quality roughage diets.

Abstract: In two experiments, each with 32 cross-bred ([Merino x Border Leicester] x Poll Dorset) wether lambs (26 to 33 kg weight range), animals were randomly assigned to one of four treatments. A mixture of lucerne chaff:oaten chaff was used as a basal diet, offered in different ratios. Animals were allowed to consume on a free-access basis in Exp. 1 or 90% of ad libitum intake in Exp. 2 in order to provide a low- (6.5 MJ ME/d) and medium- (9.5 MJ ME/d) quality basal diet, respectively. Isoenergetic amounts of lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
36
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 0 publications
10
36
2
6
Order By: Relevance
“…According to Osório and Osório (2003), the high total lipids can negatively affect meat product, once consumers have certain restrictions on the ruminants fat, mainly sheep, due to the high levels of saturated fatty acids. Studies have shown that the lipid levels of lamb meat can present great variation, especially when animals are subjected to distinct diets, such as the findings of Zeola et al (2004) using different concentrate levels (60, 45, and 30%), or diets containing different sources of roughage (PONNAMPALAM et al, 2001). However, in this study, the crude glycerin levels did not significantly affect meat lipids.…”
Section: Resultscontrasting
confidence: 55%
“…According to Osório and Osório (2003), the high total lipids can negatively affect meat product, once consumers have certain restrictions on the ruminants fat, mainly sheep, due to the high levels of saturated fatty acids. Studies have shown that the lipid levels of lamb meat can present great variation, especially when animals are subjected to distinct diets, such as the findings of Zeola et al (2004) using different concentrate levels (60, 45, and 30%), or diets containing different sources of roughage (PONNAMPALAM et al, 2001). However, in this study, the crude glycerin levels did not significantly affect meat lipids.…”
Section: Resultscontrasting
confidence: 55%
“…Unfortunately, mammals have limited ability to synthesize omega-3 fatty acids, which are necessary for their health benefits (Kris-Etherton et al, 2002). It is well known that dietary omega-3 has an important role in the maintenance of the structure of cellular membranes, improving the absorption of liposoluble vitamins (A, D, E, and K), reducing plasma triglycerides, regulating the cholesterol metabolism, and producing eicosanoids, which regulate various cellular processes (vascular and bronchial tone, gastrointestinal and uterine motility, gastric protection, urine output, blood clotting, body temperature, and inflammatory and immune processes (Ponnampalam et al, 2001). Dietary omega-3 fatty acids are also essential for normal growth and metabolism (Kris-Etherton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, nos ruminantes, parte dos ácidos graxos insaturados provenientes da dieta é saturada por meio de um processo de biohidrogenação no ambiente ruminal como forma de neutralizar o efeito tóxico desses ácidos graxos aos microrganismos ruminais. Como resultado desse processo, a classe dos ácidos graxos saturados é absorvida e incorporada ao nível de tecido muscular (Ponnampalam et al, 2001). Petrova et al (1994) salientaram que uma dieta à base de concentrado tem elevada quantidade de carboidratos rapidamente degradáveis no rúmen, fato que pode ter intensificado o gosto doce na carne dos cordeiros sob suplementação.…”
Section: Resultsunclassified